2016
DOI: 10.3390/s16060892
|View full text |Cite
|
Sign up to set email alerts
|

Millimetre-Wave Backhaul for 5G Networks: Challenges and Solutions

Abstract: The trend for dense deployment in future 5G mobile communication networks makes current wired backhaul infeasible owing to the high cost. Millimetre-wave (mm-wave) communication, a promising technique with the capability of providing a multi-gigabit transmission rate, offers a flexible and cost-effective candidate for 5G backhauling. By exploiting highly directional antennas, it becomes practical to cope with explosive traffic demands and to deal with interference problems. Several advancements in physical lay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
64
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(70 citation statements)
references
References 23 publications
0
64
0
Order By: Relevance
“…The large bandwidth of mm-wave is also accompanied by a high path loss, which necessities the use of multihop relaying across the small-cell base stations [2]. Intelligent routing methods will also be needed for the underlying applications of 5G, e.g., the Internet of Things (IoT) [3].…”
Section: Introductionmentioning
confidence: 99%
“…The large bandwidth of mm-wave is also accompanied by a high path loss, which necessities the use of multihop relaying across the small-cell base stations [2]. Intelligent routing methods will also be needed for the underlying applications of 5G, e.g., the Internet of Things (IoT) [3].…”
Section: Introductionmentioning
confidence: 99%
“…Heterogeneous network (HetNet), which could provide efficient spatial reuse, together with the disruptive technologies, such as massive-MIMO and millimeter-wave (mm-wave) communication, are considered as a promising solution [2]. In current cellular networks, backhaul data traffics between cell base-stations (BSs) and the central macro-cell BS are normally fulfilled using high capacity fiber connections.…”
Section: Introductionmentioning
confidence: 99%
“…However, in future HetNets the cost of fiber infrastructures between macro-cell BS and small-cell BSs, which provide high capacity within a small spatial coverage, would be prohibitively high, simply due to the fact of a huge number of small-cells and their high flexibility, e.g., the site of a small-cell can be moved according to the change of user distributions. As a consequence, great efforts have been devoted to the wireless backhaul, especially in mm-wave band [2] [3] because the larger available frequency bandwidth is able to provide higher spectrum efficiency [4].…”
Section: Introductionmentioning
confidence: 99%
“…Most studies on microwave and mm-wave dual-band transmission have focused on how to improve network layer performance metrics of cellular access or backhaul networks by using the high-bandwidth, highly directional mm-wave links [9,13]. For example, the authors in [7] posed the problem of optimal resource allocation in a cellular setting in the dual microwave and mm-wave band, and showed that certain network level performance parameters, e.g., the number of simultaneously supported users and the link connection probability, are vastly improved with their proposed solution.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, microwave links are much more reliable due to rich scattering and diffraction, but cannot support as high rates as the mm-wave links. Thus, in a dual-band setting, conventional traffic and control information can be reliably communicated over microwave links, and high data-rate traffic can be sent through mm-wave links [2,7,[9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%